Wielokadencyjność bez afiliacji partyjnej? Spostrzeżenia po reelekcjach „wiecznych prezydentów” w 2014 r. - Drzonek, Maciej (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
Od 2002 r. prezydenci miast są wybierani co 4 lata w wyborach bezpośrednich. W 30 miastach na prawach powiatu w latach 2002–2010 wybierano na prezydentów te same osoby. Określa się ich mianem „wiecznych prezydentów” (wielokadencyjni prezydenci). W 2014 r. trzech z nich zrezygnowało z walki o reelekcje, a dziesięciu przegrało wybory, a zatem siedemnastu kolejny raz wygrało wybory. Ich zwycięstwa są punktem wyjścia do określenia pozycji partii politycznych i komitetów pozapartyjnych na lokalnych scenach politycznych. Przyjęto bowiem założenie, że pozycja partii politycznej jest mocna, o ile dotychczasowy wielokadencyjny włodarz miasta skutecznie ubiega się o reelekcję, formalnie ją reprezentując. A contrario – jeśli inkumbent w walce o reelekcję wybiera start z komitetu pozapartyjnego (komitet wyborczy wyborców albo komitet wyborczy organizacji pozarządowej) to świadczy to o słabszej pozycji partii politycznej w danym mieście. Analiza pokazała, że w 2014 r. większość „wiecznych prezydentów” dokonała reelekcji, startując w wyborach jako reprezentanci komitetów pozapartyjnych. Tylko w dwóch przypadkach (Gdańsk, Świnoujście) fotele włodarzy miast zostały zajęte przez partyjnych inkumbentów.

Since 2002, town mayors in Poland have been elected in direct elections every four years. In thirty towns with county rights the same persons were elected in the years 2002–2010. They are named ‘everlasting mayors’ (multi-term mayors, incumbents). In the 2014 local elections three of them resigned from the campaign for re-election, ten ‘everlasting mayors’ lost the elections and seventeen of them won the elections once again. Their successes provide the starting point for determining the position of political parties and nonpartisan committees on local political scenes. The assumption is made that the political position of parties is powerful if the ‘everlasting mayor’ is effective in trying to gain re-election while formally representing this party on the local political scene. And conversely – parties have a weaker political position on the local political scene when the incumbent prefers to lead a nonpartisan election committee in the rivalry for re-election (an electoral committee of voters, or an electoral committee of a nongovernmental local organization). The final conclusion of the analysis is the following: in the 2014 local elections in Poland most of the ‘multi-term mayors’ were re-elected as representatives of nonpartisan committees. Only in two cities (Gdańsk, Świnoujście) were mayors’ seats won by party political incumbents.
Multiple terms in office without political party affiliation? Remarks following the Re-election of ‘everlasting mayors’ in 2014
Keywords: polityka lokalna; wybory prezydentów miast; wielokadencyjni prezydenci; władza lokalna; local politics; mayor of town elections; multi-term mayors; local power